2007
DOI: 10.1111/j.1600-6143.2006.01654.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of CCR1 Blockade on the Progression of Chronic Renal Allograft Damage

Abstract: The biology of chemokines and their receptors have been linked to the development of chronic allograft damage. Effects of CCR1 antagonist BX 471 were studied in a Fischer to Lewis renal transplantation model at days 10, 21 and 42 after transplantation. BX 471 treatment did not effectively reduce signs of acute rejection at day 10 but significantly improved allograft function and morphology at day 21 posttransplantation. When therapy was initiated on day 21 after transplantation, glomerulosclerosis and tubuloin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 50 publications
2
62
0
Order By: Relevance
“…In renal transplants with delayed graft function, early expression of RANTES with the consecutive invasion of CCR1-positive cells was associated with subsequent renal fibrosis, tubular atrophy and worse renal allograft outcome (320). Consistent with this, experimental allograft nephropathy was reduced by early treatment with the CCR1 antagonist BX 471 (321). Another experimental approach of chemokine antagonism involved Met-RANTES, a chemokine receptor antagonist that blocks the effects of RANTES.…”
Section: Chemokines and Innate Immunitymentioning
confidence: 64%
“…In renal transplants with delayed graft function, early expression of RANTES with the consecutive invasion of CCR1-positive cells was associated with subsequent renal fibrosis, tubular atrophy and worse renal allograft outcome (320). Consistent with this, experimental allograft nephropathy was reduced by early treatment with the CCR1 antagonist BX 471 (321). Another experimental approach of chemokine antagonism involved Met-RANTES, a chemokine receptor antagonist that blocks the effects of RANTES.…”
Section: Chemokines and Innate Immunitymentioning
confidence: 64%
“…[54][55][56] The correlation between enhanced abundance of biglycan and reduction of organ function in various sterile inflammatory renal diseases has been particularly well documented. 8,19,[55][56][57][58] Upregulation of biglycan in aortic stenosis, characterized by lipid accumulation and inflammation, 59 results in enhanced synthesis of phospholipid transfer protein via stimulation of TLR2. 60 Furthermore, higher levels of biglycan in cardiac transplant coronary arteriopathy, 58 severe ocular surface disease 61 and in adipose tissue 62 suggest a role for biglycan in the perpetuation of inflammation.…”
Section: Decorin As Endogenous Ligand Of Tlr2/tlr4 and Tgfβ1 Inhibitomentioning
confidence: 99%
“…8,19,[55][56][57][58] Upregulation of biglycan in aortic stenosis, characterized by lipid accumulation and inflammation, 59 results in enhanced synthesis of phospholipid transfer protein via stimulation of TLR2. 60 Furthermore, higher levels of biglycan in cardiac transplant coronary arteriopathy, 58 severe ocular surface disease 61 and in adipose tissue 62 suggest a role for biglycan in the perpetuation of inflammation. Further studies concerning the mechanisms of biglycan-driven inflammation in those pathophysiological processes would improve our understanding of how sterile inflammation is triggered.…”
Section: Decorin As Endogenous Ligand Of Tlr2/tlr4 and Tgfβ1 Inhibitomentioning
confidence: 99%
“…28,30 Occupancy of ␣ v ␤ 3 integrins can decrease monocyte binding capacity to ICAM-1 and VCAM-1, which are up-regulated in acute allograft rejection. 21,49,51,54 We and others 17,32 have shown that tubular osteopontin expression is significantly enhanced in renal biopsies with acute rejection and could be correlated with interstitial macrophage infiltration and cell proliferation. Osteopontin is an extracellular matrix protein containing an RGD sequence, which can interact with at least three different ␣ v -containing integrins, ␣ v ␤ 1 , ␣ v ␤ 3 , and ␣ v ␤ 5 ; its migratory activity seems to depend on the presence of a functional ␣ v ␤ 3 on the cell surface.…”
Section: Discussionmentioning
confidence: 95%
“…In the Fisher 344 to Lewis (F344-LEW) model, the right kidney of the recipient was left in place to enhance allograft rejec-tion 32 and to serve as a control for the effect of S247. In the BN-LEW model, nephrectomy was performed bilaterally.…”
Section: Animals and Renal Transplantationmentioning
confidence: 99%